2021
DOI: 10.3389/fendo.2021.677701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on Male Reproductive System – A Systematic Review

Abstract: BackgroundAngiotensin-converting enzyme II (ACE2), a receptor for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) to enter host cells, is widely expressed in testes and prostate tissues. The testis and prostate produce semen. At present, there are contradictory reports about whether SARS-CoV-2 can exist in the semen of infected men.ObjectiveTo provide a comprehensive overview of the topic of whether COVID-19 can impact on male reproductive system.MethodsWe reviewed the relevant publications on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 90 publications
2
93
1
2
Order By: Relevance
“…This study was designed to identify potential detrimental effect of the SARS-CoV-2 vaccine by Pfizer on male fertility. Although previous reports demonstrated increased risk of sperm count abnormalities amongst active and recovered SARS-CoV-2 infected patients (Gacci et al, 2021;He et al, 2021;Li et al, 2020), in the present study we could not demonstrate any evidence of adverse effects on semen parameters following COVID-19 vaccination.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…This study was designed to identify potential detrimental effect of the SARS-CoV-2 vaccine by Pfizer on male fertility. Although previous reports demonstrated increased risk of sperm count abnormalities amongst active and recovered SARS-CoV-2 infected patients (Gacci et al, 2021;He et al, 2021;Li et al, 2020), in the present study we could not demonstrate any evidence of adverse effects on semen parameters following COVID-19 vaccination.…”
Section: Discussioncontrasting
confidence: 89%
“…Nonetheless, most studies published so far found no viral traces in the semen of both active disease and recovered patients and a recent review determined the likelihood of SARS-CoV-2 presence in the semen of COVID-19 patients is very small. (Guo et al, 2021;He et al, 2021;Holtmann et al, 2020;Kayaaslan et al, 2020;Pan et al, 2020;Paoli et al, 2020;Song et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the preferential binding SARS-CoV-2 spike protein has for ACE2 receptors, it is interesting to note that in addition to the high expression of ACE2 receptors in the lungs, several studies have found increased expression of ACE2 receptors in the prostate epithelium, kidneys, and testes, showing that the male genitourinary system may serve as a target-rich environment for SARS-CoV-2 spike protein binding [21][22][23][24]. In their review on the effects of COVID-19 on the male reproductive system, He et al found damage to testicular cells and impaired spermatogenesis and proposed that the pathology is due to both direct interactions of SARS-CoV-2 and ACE2 receptors, as well as systemic inflammatory and immune responses to infection [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although these results did not reveal the paternal immune signal per se, they point to possible scenarios for the realization of the effects of antigenic challenge on the reproductive function of men, which includes viral infections. For example, COVID-19 interferes with spermatogenesis, reduces sperm quality in moderately infected patients, and poses health risks to their offspring [43][44][45]. Thus, the IVF model can be effective for studying the effects of antigens of different natures on male reproduction and the development of their offspring.…”
Section: Discussionmentioning
confidence: 99%